2005
DOI: 10.1007/s00381-004-1108-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of metopic synostosis

Abstract: Mild forms of metopic synostosis can be successfully treated with burring of the metopic ridge alone. Severe forms require craniofacial reconstruction and may be associated with other congenital abnormalities, additional synostosis, and developmental delay. In all cases, the operative procedure must be tailored to the nature and severity of the deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…Surgical treatment of metopic craniosynostosis includes remodeling of the forehead and advancement (Aryan et al, 2005;Di Rocco et al, 2013;Engel et al, 2011;Keshavarzi et al, 2009). At our department we prefer fronto-orbital advancement specially applied to trigonocephaly and the insertion of an inter-orbital bone graft, if necessary, to correct the hypotelorism (Engel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment of metopic craniosynostosis includes remodeling of the forehead and advancement (Aryan et al, 2005;Di Rocco et al, 2013;Engel et al, 2011;Keshavarzi et al, 2009). At our department we prefer fronto-orbital advancement specially applied to trigonocephaly and the insertion of an inter-orbital bone graft, if necessary, to correct the hypotelorism (Engel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, metopic synostosis refers to a suture pathology, but trigonocephaly is a clinical entity (6). Similarly, Aryan et al reported that in mild forms of metopic synostosis, there is only prominent ridging of the metopic suture, whereas severe cases have frontal narrowing and hypotelorism (1). A palpable metopic ridge was defined by Shimoji et al as the most important physical sign in a series of mild trigonocephalic patients (13).…”
Section: █ Discussionmentioning
confidence: 98%
“…On the one hand, FOA is a standardized and well-established surgical technique, which allows the abnormally closed suture to be opened and movement of the affected bone segments in the desired direction (Aryan et al, 2005;Fearon et al, 2009). On the other hand, FOA is usually accompanied with substantial blood loss and the need for RBC transfusion due to the infant's low circulating blood volume (Maugans et al, 2011;Oppenheimer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Objectives for treatment include expansion and advancement of the supraorbital bandeau, widening of the temporal dimensions and rounding the forehead, and different surgical techniques have been described (Aryan et al, 2005;Di Rocco et al, 2013Metzler et al, 2014). At our unit, trigonocephaly is treated with fronto-orbital advancement (FOA) between the ages of 8 and 10 months (Engel et al, 2012(Engel et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%